Penggunaan Model Pendidikan Holistik dalam Meningkatkan Ibadah Wajib Santri Putri Pondok Pesantren Modern Kreatif Muhammadiyah Boarding School Tahun Pelajaran 2024/2025 - Nugrah, Nugrah; Syamsiar, Syamsiar (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to determine the effectiveness of using a holistic education model in improving the obligatory worship of female students at the Muhammadiyah boarding school in the 2024/2025 academic year. The holistic education model is seen as an approach that touches all aspects of student development, both spiritual, emotional, and social. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, self-assessment and documentation. The results of the study showed that there was a significant increase in the implementation of obligatory worship of female students after the implementation of the holistic education model. Thus, it can be concluded that the holistic education model is effective in improving the quality of obligatory worship of female students. These findings are expected to be a reference in the development of a more comprehensive and transformative Islamic boarding school education system.